2022
DOI: 10.21203/rs.3.rs-1627881/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating the Rights-based and Capability Approaches in the Analysis of Maternal Healthcare Utilization in sub-Saharan Africa: A Multilevel Modelling Study

Abstract: Background: The rights-based and capability approaches have received increased attention relative to maternal health in the aftermath of the 2015 Millenium Development Goals (MDGs). This is in view of the sub-optimal progress gained in reducing maternal and child mortality, especially in developing countries. Despite the combined potential of these models, limited empirical studies testing their viability in maternal health exist. This is what this study sought to accomplish. Method: We combined several datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is plausible that women who live in countries with high social globalisation index would be more likely to use maternal healthcare compared to their counterparts who do not. Several studies have demonstrated the crucial role played by exposure to the media as well as civil and socio-economic rights in maternal and reproductive health matters [33][34][35] . Promotion of civil, media, technology, and communication freedoms shape culture, enhance citizen awareness about their rights, and influence national politics which may in turn lead to better provision, access, and utilisation of health services.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that women who live in countries with high social globalisation index would be more likely to use maternal healthcare compared to their counterparts who do not. Several studies have demonstrated the crucial role played by exposure to the media as well as civil and socio-economic rights in maternal and reproductive health matters [33][34][35] . Promotion of civil, media, technology, and communication freedoms shape culture, enhance citizen awareness about their rights, and influence national politics which may in turn lead to better provision, access, and utilisation of health services.…”
Section: Discussionmentioning
confidence: 99%